THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND READING COMPREHENSION OF THE FIRST YEAR STUDENTS OF SMPN 1 CISARUA BANDUNG BARAT - Pilli Parliyah; Tanty Khotimah (IKIP Siliwangi, 2020)
The objective of this study is to know the correlation between students’ motivation and their achievement in reading comprehension. The research used quantitative method and correlational research as design. The population of the study was the seventh grade students of Junior High School 1 cisarua, Kabupaten Bandung Barat in academic year 2017/2018 with total number 395 students and the sample in this study is 32 students. Instruments for data collection were the questionnaire to find out students’ motivation and the reading comprehension test. Pearson Product Moment was used to analyze the data and the hypothesis testing was computed by applying SPSS version 22. It was found that there is a significant correlation between students’ motivation and their achievement in reading because the correlation coefficient was 0.658. It was classified into high correlation . Thus, there is a significant correlation between reading motivation and reading motivation. The result can be interpreted that students’ motivation had strong effect to reading comprehension skill. It is suggested the English teachers have to create teaching strategies that will motivate the students to read in class.Keywords: Correlation, students’ motivation, reading, achievement.